La contaminación visual publicitaria y elementos atípicos del sector comercial en la ciudad de Latacunga”. - Chicaiza Tuso, Lenin Abel (2024)
The proposal is located in the Latacunga city and arises from an visual pollution exhaustive analysis present in the commercial sectors from city. To address this problem, it was applied a methodology, which incorporates environmental approaches, integrating theories, concepts and practices related to environmental psychology, architecture, urban planning and design. Portella (2014). In this context, it was assessed the municipal regulations from Latacunga, they regulate aspects, such as: informal commerce, the appropriate location from wiring and infrastructure, as well as general advertising by businesses. The aim was to analyze the impact this regulation on the life quality from city's inhabitants, who require the support and guidance from authorities.